Technology assessment in patent search engine: An effort for reading invention opportunities and product innovation - Ferianto Ferianto; Luthfina Ariyani; Tommy Hendrix (Universitas Negeri Surabaya, 2022)
Examining the technology opportunities of the patent search engine throughtechnology assessment can help the companies determine the appropriate directionof further technology development to open-up business opportunities in the future.This paper aims to conduct a technology assessment on patent search enginetechnology to understand the trends of patent search engine development. Thisstudy used a qualitative research methodology with descriptive analysis accordingto literature studies and patent analysis. Innography software was used to derive thepatent data. The results showed the technology development trend, key playersinvolved, and the competitors related to patent search engine technology. Theanalysis has been conducted on IPRs data of 38 registered in patent search enginefields to identify several aspects, such as inventor, organisation, IP class, fillingyear, patent strength and factor, portfolio strength, and GEM finder. The patentdatabase becomes an asset to define many technical processes from research anddevelopment. Conducting patent analysis in patent search engines is essential tocapture opportunities for invention and innovation in related field technology.